Discrepancies between supervisor self-evaluations and staff perceptions of leadership: a cross-sectional study in healthcare - Nguyen Hoang Long; Julie Sochalski (BMC Nursing)
Abstract Background Employees’ perceptions of their supervisors’ leadership influence their conduct and daily performance. These perceptions often conflict with leaders’ self-assessments. Understanding this incongruency can help leaders improve their leadership skills. This study aimed to assess the congruency between frontline healthcare staff’s and supervisors’ perceptions of leadership styles. Methods This cross-sectional study was conducted between January 2021 and June 2022. Data were collected from a convenience sample of 574 professional and technical staff (nurses, midwives, and technicians) and 93 direct supervisors recruited from all seven hospitals of the Vinmec Healthcare System, which is the largest private healthcare system in Vietnam. Leadership style was assessed using the Multifactor Leadership Questionnaire (MLQ 5X). Results Study findings revealed similarities and differences in perceptions of leadership between staff and supervisors. Both groups agreed that transactional contingent reward behaviors were most frequently used, as indicated by mean scores above 2.5, whereas laissez-faire behaviors were least often utilized, with the lowest overall ratings (supervisors: 0.92 ± 0.67; staff: 1.23 ± 0.78). However, supervisors’ scores were significantly higher than those of their staff for almost all leadership components, with large and significant mean differences observed in areas such as individualized consideration (mean difference = 0.63, t = 9.34, p <.001). Notably, staff rated supervisors as using laissez-faire behaviors more frequently than their supervisors assumed they did, with a statistically significant difference (t = − 3.96, p <.001). Regarding leadership outcomes, supervisors believed that their leadership style was more effective than their staff perceived it, as evidenced by higher scores for effectiveness (2.94 vs. 2.72, t = 3.46, p <.001), satisfaction (3.02 vs. 2.73, t = 3.90, p <.001), and extra effort (2.98 vs. 2.57, t = 6.49, p <.001). Conclusion Supervisors should recognize their leadership styles and how they are perceived by staff, using feedback as a basis for self-improvement and ensuring their intentions are clearly communicated. In nursing, 360-degree feedback and reflective practices may help narrow leadership perception gaps. Future research should examine factors underlying these discrepancies and assess whether improving alignment enhances team performance and care quality. Clinical trial number Not applicable.